The in vitro Efficacy of Two Microbial Strains and Physicochemical Effects on their Aflatoxin Decontamination in Poultry Feeds - Tebetyo, Zakia; Bogere, Paul; Nabulime, Margaret M.; Kaaya, Archileo N.; Gnonlonfin, Benoit; Ntale, Mohammed; Nakavuma, Jesca (My University, 2020)
Contamination of animal feeds with aflatoxigenic fungi is a challenge to livestock farmers worldwide. Aflatoxins are very toxic fungal metabolites that are associated with carcinogenic, mutagenic, teratogenic, and estrogenic effects. The toxins affect animal productivity and may lead to deaths, causing enormous economic losses. Aflatoxin decontamination is a challenge to the feed industry, despite the several approaches available. This study investigated the efficacy of two microbial isolates, Bacillus spp (B285) and Yeast strain (Y833), in reducing Aflatoxin concentration in poultry feeds in comparison with a commonly used commercial chemical binder, Bentonite. The influence of the poultry feed matrix, pH, and temperature on the aflatoxin reducing activity by the two microorganisms was also explored. Results: The in vitro studies showed that the two microorganisms and the chemical binder reduced aflatoxins by over 74% of the original concentration. The chemical binder registered the highest reduction at 93.4%; followed by Y833 (83.6%), then the combination of Y833 and B285 (77.9%); and lastly B285 (74.9%). There was no significant (p>0.05) influence of temperature on the toxin reducing capacity of all the agents tested. The pHs 4.5 and 6.5 did not have a significant effect on the performance of both chemical binder and biological agents, however, the former performed better at pH 6.5 with 95% aflatoxin reduction compared to the microorganisms. The aflatoxin reducing activity was lower in presence of feeds compared to that in Phosphate Buffered Saline except for Y833 where no difference was observed. Conclusions: Although the feed components affected the aflatoxin reducing capacity of the test materials, the chemical binder was more effective than the microbial agents. Yeast strain was more effective than the bacterial strain in reducing the aflatoxin levels, however, both are promising strategies for countering the aflatoxin challenges in animal feeds. In response to the advocacy for use of biological control agents, there is need for more investigations to establish the safety of the microorganisms, the mechanism of decontamination and safety of the products; the optimum concentrations that can reduce aflatoxins in feeds to permissible levels and the effect of the toxin contamination levels on microbial efficiency.
Keywords: animal feeds; aflatoxigenic fungi; livestock farmers